Studi Karakteristik Marshall pada Aspal Porous dengan Penambahan Abu Cangkang Kopi sebagai Filler - Sulaiman, Sulaiman; Gani, Fauzi A.; Miswar, Khairul; Gusrizal, Gusrizal; Maulana, Adi (Portal: Jurnal Teknik Sipil, 2023)
The type of pavement used in Indonesia is generally flexible pavement. Porous asphalt is one of the flexible pavement layers. Porous asphalt is a mixture of asphalt concrete with a high content of air voids in the mixture. The purpose of the study was to determine the composition and characteristics of porous asphalt with coffee shell substitution as a filler. Aggregate gradation used open gradation or uniform graded with variations in asphalt content of 3.2%, 3.7%, 4.2%, 4.7% and 5.2% before being substituted for coffee shells, using 60/70 penetration asphalt as a binder. The results of testing and calculation of Marshall parameters to determine KAO, obtained an optimum asphalt content of 4.7% with a stability value of 804 kg, flow 3.3 mm, VIM 19.2%, and MQ 249.4 kg/m. After the KAO was obtained, the specimens were made with variations of coffee shell substitution of 0.5%, 1%, 1.5%, 2% and 2.5%. Marshall test results obtained the optimum composition of coffee shell content at 1% composition with a stability value of 1474 kg, flow 3.1 mm, VIM 13.8%, and MQ 475.6 kg/m. The optimum coffee shell content is determined by the results of the ups and downs of a graph. The test results are evidenced by the increase in the value of the graph on the value of stability, flow, and MQ.